A mechanism for identifying the guilt agent in a network using vector quantization and skew Gaussian distribution - Praveen Kumar, P; Srinivas, Y; Vamsi Krishna, M (International Journal of Engineering and Technology, 2018)
The recent state of art technologies has facilitated towards the ease of transfer of information from source to destination in a most comfortable and optimized medium. The channel transmitting discrepancies are rotted out by the sophisticated mechanisms that are being used currently using fiber optical cables etc… However sophisticated transmission mechanisms are available, the data transmission is always under threat due to intruder’s hackers and guilt agents, who try to either steal the information, override the information or share the information to miscreants. Therefore techniques are to be developed to identify these guilt agents so that the data transmission can be transformed in a more secure way without any pitfalls. This paper addresses in this direction by proposing models based on vector quantization and statistical models.